Wage dynamics and inequality in the Brazilian formal labor market - Amanda Cappellazzo Arabage; André Portela Souza (EconomiA, 2019)
This paper investigates the decrease in wage inequality among working age men in the Brazilian formal labor market by decomposing it into its permanent and transitory components. The permanent component refers to workers' productivity characteristics such as education and abilities, whereas the transitory component relates to noise caused by economic instability. We use data from the Annual Reports of Social Information (RAIS) from 1994 to 2016, covering periods of both economic instability and stability. Our proposed model includes year and cohort specific effects in both components and we use minimum distance methods to estimate our parameters of interest. Overall we observe a downward trend in wage inequality levels for most cohorts during the entire period. However, different sources are associated with this decrease in different sub-periods. This decline can be attributed to reductions in the transitory component from 1994 to 2005 (related to the economic stabilization process) and in the permanent component from 2010 to 2016. Moreover, our results suggest that the permanent component has an important role in explaining the wage inequality level in Brazil, especially considering older cohorts, even though its share in terms of total variance has decreased over the 2010s. Finally, we show that age and education are accountable for a great share of permanent inequality, with this percentage being even greater for younger cohorts, although their relative importance also decreased over the years.
Keywords: F31; F34; G15; G18; J03; J06; O05; 330; Wage inequality; Variance decomposition; Formal labor market